Mechanism of grain refinement in ferritic stainless steel welds: between dendrite fragmentation, grain detachment and heterogeneous nucleation - Amuda , Muhammed Olawale Hakeem; Mridha , Shahjahan (David Publishing, 2011)
The morphology of the grain structure in fusion welds is generally columnar and elongated. This structure is highly anisotropic and makes weld metal susceptible to centerline hot cracking and poor notch impact toughness particularly in welds that are prone to brittle fracture such as the ferritic stainless steel welds. An equiaxed grain structure is preferred in weld metal. Considerable studies have been undertaken to produce equiaxed grains in welds using different welding techniques. These studies established that grain refinement in welds has a linear relationship to the density of equiaxed grain in the columnar-equiaxed transition morphology at both the top surface and cross section of the weld. The increased density of equiaxed grains is due to the control of local solidification parameters both at the advancing solid/liquid interface and at the centre of the weld pool. Several mechanisms ranging from heterogeneous nucleation to dendrite fragmentation and grain detachment have been put forward to explain the phenomenon of grain refinement in fusion welds. These mechanisms are quite contrasting. In the present effort, a cross evaluation of these mechanisms is undertaken to identify the dominant mechanism. The evaluation suggested that other than in certain cases of compositional/ constitutional undercooling, dendrite fragmentation and grain detachment appear to be the controlling mechanisms except when specific steps are taken to introduce nuclei to promote heterogeneous nucleation.